Evaluation of relationship of intuitive eating and eating awareness with body mass index and anthropometric measurements in adults - Dağ, Ayhan; Özören, Aliye; Baran, Özlem (Progress in Nutrition, 2023)
Objective: This study was conducted to assess effects of intuitive eating and eating awareness on body mass index (BMI) and anthropometric measurements (nutritional habits, food choices and amount of consumption) in adults.Material and method: This study was conducted with adult residents from Lefkoşa, North Cyprus Turkish Republic between September, 2020 and November, 2020. Overall, 386 subjects were recruited to the study, including 247 women and 139 men. The demographic characteristics were recorded using a data sheet and anthropometric measurements were performed in all subjects. The Intuitive Eating Scale-2 (IES-2) was used to assess level of intuitive eating behavior while the Eating Awareness Scale-30 (EAS-30) was used to assess eating awareness.Findings: It was found that there were significant, negative correlations between IES-2 scores and body weight and BMI in female subjects (p